Alliances and digital transformation are crucial for benefiting from dynamic supply chain capabilities during times of crisis: A multi-method study - Yogesh Dwivedi (International Journal of Production Economics, 2024)
During times of crisis, businesses need strategic partnerships and digital transformation to survive. Understanding how digital transformation and alliance management capability can work together to enhance supply chain capabilities during a crisis is important. We have developed a theoretical framework that explains how the alliance management capability, under the mediating influence of digital transformation, helps build supply chain capabilities for unprecedented crises. This framework highlights key enablers such as alliance management capability, digital transformation, supply chain agility, and supply chain adaptability that are essential for organisational performance. We tested our theoretical model using a survey of 157 individuals working in the manufacturing industry in India. Our findings suggest that combining alliance management capability and digital transformation enhances supply chain capabilities, which improves an organisation's ability to respond to crises. Moreover, digital transformation, supply chain agility, and adaptability are critical determinants of organisational performance during crises. Therefore, companies that use digital technologies to increase their agility and adaptability are more likely to perform well during times of crisis. To collect qualitative data, we interviewed key participants (n = 27) and identified four key enablers for a digital transformation strategy for supply chains: coordination, digital leadership, digital culture, and digital talent management. Our study offers a detailed understanding of the dynamic capability view in digital transformation, highlighting key drivers for competitive advantage.